BIOREMEDIATION AND REMEDIATION WITH ACID RESIDUAL FLUID - Rondon, Josimara Nolasco; Aguiar, Mariane Baia de; Pimenta, Talita Thais Correia; Otsubo, Helena de Cassia Brassaloti; Thomazelli Junior, Ismael; Rondon, Marcelo Nolasco; Fabri, João Roberto; Carvalho, Cristiano Marcelo Espinola; Morais, Digelson Pazeto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The aim of this study was to evaluate the feasibility of using bioremediation and F. moliniforme in remediation of compounds made from plastics and other polymers using waste pollutants. The survival analyzes for survival / growth resistance and pollutants in the concrete for 30 days was observed. We evaluated the size of the colonies in battery fluid (pH = 0.1) and weekly reviews of pH in three 1000 mL volumetric flasks, having in each 133 mL of battery + 100 mg of Fusarium moliniforme. To review the development and formation of colonies of microorganisms miners, we used 320g samples distributed in three trays concrete material. And was inserted solution of green algae free and Fusarium moliniforme life. With mixing the solution with a battery for inoculation of nutrient Fusarium moliniforme in an alkaline environment (pH between 10 and 14) means. Observed the growth of colonies and changing an pHs for a neutral medium (pH 7.0): 78 colonies. In three days sleeve dilution initiated and completed processing within 30 days. This process occurred with a combination of solution and battery residual crushed lime construction and promoted the transformation of the solid phase in the liquid phase in only 30 days. After 2 days s solution was neutralized (pH 7) and thus remaining constant. The battery solution can be neutralized with the addition of carbonates for remediation. The combination of battery solution more carbonates digested the solid state of natural rubber surgical glove can be reused by the industry to produce new products. Fusarium moliniforme biorremediador should be used as the treatment of contaminated soils ex situ, bioadition and bioaugmentation because this fungus neutralized acidic pH of contaminated soils with concrete residue.